Pulsed Electric Field Extraction of α and β-Acids From Pellets of Humulus lupulus (Hop) - Ntourtoglou, George; Tsapou, Evangelia Anastasia; Drosou, Fotini; Bozinou, Eleni; Lalas, Stavros; Tataridis, Panagiotis; Dourtoglou, Vassilis (Frontiers in Bioengineering and Biotechnology, 2020)
This paper investigates the process of extracting hop pellets (hops) utilizing the pulsed electric field (PEF) technique and the contrasting effects of the technique between two distinct hop varieties (one bitter and one aromatic). The effect of PEF on the extraction was evaluated by measuring the concentration of α-acids and β-acids (humulones and lupulones). Regarding the aromatic character, the hop’s volatile caryophyllene, humulene and β-myrcene were analyzed both with and without employing the PEF treatment. In order to analyze the acids and the volatile fraction, the analytical method of UV–vis spectrophotometry was applied followed by gas chromatography coupled with mass spectrometry. For the second technique, the extracts were previously purified through a Graphitized Carbon Black syringe for Solid Phase Extraction. The results revealed that PEF had a positive impact on the alpha acids of bitter hops by increasing the extraction rate of these acids by 20%, while the volatiles demonstrated an increase of 5.6 and 7.4% for humulene and caryophyllene, respectively. Concerning the aromatic variety of hops, the PEF treatment appeared to have no noteworthy effects.